2007
DOI: 10.1002/chem.200600396
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigations on the Catalytic Hydrosilylation of Carbon Dioxide with Ruthenium Nitrile Complexes

Abstract: Poisonous mushrooms. The deadly toxin orellanine is present in the toadstools Cortinarius orellanus and C. rubellus (see photo) as the water‐soluble 4,4′‐diglucoside. Its biosynthesis starts from anthranilic acid as has been shown by application of 15N/14N isotope ratio mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 122 publications
(85 reference statements)
2
70
0
2
Order By: Relevance
“…This accounts, at least in an approximate way, for the fact that these compounds do not enter or leave the reaction mixture as a gas. [35] Also, the vibrational partition function contribution to the Gibbs free-energy values was omitted as the calculated vibrational spectra of the complexes were found to exhibit extremely small restricted rotational frequencies. Effects of anharmonicity and numerical accuracy, therefore, would lead to artifacts in statistical thermodynamics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This accounts, at least in an approximate way, for the fact that these compounds do not enter or leave the reaction mixture as a gas. [35] Also, the vibrational partition function contribution to the Gibbs free-energy values was omitted as the calculated vibrational spectra of the complexes were found to exhibit extremely small restricted rotational frequencies. Effects of anharmonicity and numerical accuracy, therefore, would lead to artifacts in statistical thermodynamics.…”
Section: Methodsmentioning
confidence: 99%
“…Effects of anharmonicity and numerical accuracy, therefore, would lead to artifacts in statistical thermodynamics. [35] To evaluate the influence of the solvent on the relative energies, singlepoint energies were computed employing the COSMO [48] solvation model with the dielectric constant of acetone and the catalysis reaction solvent, CH 2 Cl 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] A variety of catalysts have been discovered and developed for this reaction, including complexes of Co, 4 Cu, [5][6][7][8] Ir, [9][10][11][12][13][14] Ni, [15][16][17] Pd/Pt, 18 Rh, 19 Ru, [20][21][22][23][24][25] Sc, 26 Zn, [27][28][29] and Zr, 30 frustrated Lewis pairs, [31][32][33][34][35][36] organocatalysts, [37][38][39][40][41][42] alkali metal carbonates, 43 and even polar solvents such as DMF. 38 These reactions result in various reduction products including silyl-formates, -acetals, andethers, CO, and methane.…”
Section: Introductionmentioning
confidence: 99%
“…A paper by Deglmann et al 99 has described both experimentally (by using in situ IR spectroscopy) and theoretically (by DFT calculations with an Me 3 SiH model), the catalytic hydrosilylation of carbon dioxide by Me 2 PhSiH with ruthenium nitrile complexes mer-(RuX 3 (MeCN) 3 ) and cis/trans-(RuX 2 (MeCN) 4 ) with X = Br, Cl. They showed that the key steps of the reaction are the transfer of the Me 3 Si moiety to a coordinated halide ligand, resulting in an L n RuH-(XSiMe 3 ) intermediate, CO 2 coordination to Ru in a side-on manner, Me 3 Si transfer to CO 2 , and reductive elimination of the formoxysilane product Me 3 SiOCHO (see Figure 16).…”
Section: Reactions With Electrophilesmentioning
confidence: 99%